THE POSITION OF MAQASID AL-SHARI’A ON FIQH OF MINORITIES - Wahib, Moh.; Samin, Sabri; Barsihannoor, Barsihannoor; Shuhufi, Muhammad (Jurnal Diskursus Islam, 2020)
This paper elaborates in depth on the position of maqasid al-syari'ah towards minority fiqh. This research is a library research, descriptive in nature. This research uses normative (syar'i) and sociological theological approaches. Primary data sources are data obtained through literature studies with primary data taken from the Koran, hadith, jurisprudence books, books that study minority fiqh or others that are related to this research. The results showed that the position of maqasid al-syari ah is the foundation and foundation for the concept of minority fiqh. The format of the rules of maqasid al-syari'ah contained in minority jurisprudence, namely: First: al-taysir waraf' al-haraj (eases and raises difficulties). Second: tagayyur al-fatwa is a change in fatwa. Third: tanzil al-hajah manzilah aL-darurat (Needs occupy an emergency). Fourth: 'Urf or customs in society. Fifth: Annazru ila al-Ma'alat (seeing the legal consequences). Sixth: The congregation as a judge.